1976
DOI: 10.1097/00000658-197611000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Changing Clinical, Pathologic, Therapeutic, and Survival Patterns in Differentiated Thyroid Carcinoma

Abstract: Records of 792 patients with differentiated thyroid carcinoma seen at the Lahey Clinic Foundation over a 40-year period were analyzed; 631 patients had a minimum followup period of 15 years. Differentiated types currently constitute nearly 90% of thyroid carcinomas. The clinical presentation has improved substantially through the years, and the results of treatment generally have improved. The per cent of patients with primarily incurable and locally unresectable disease or distant metastases has decreased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
119
2
7

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 319 publications
(140 citation statements)
references
References 17 publications
12
119
2
7
Order By: Relevance
“…The excellent outcomes reported by the Lahey clinic in 1976 (5% mortality at 10 years) were supported by findings from other major groups and remain pertinent to this day [7,8].…”
Section: Prace Poglądowesupporting
confidence: 55%
“…The excellent outcomes reported by the Lahey clinic in 1976 (5% mortality at 10 years) were supported by findings from other major groups and remain pertinent to this day [7,8].…”
Section: Prace Poglądowesupporting
confidence: 55%
“…Christensen, et al, 10 reported 94% in a defined population from Sweden. Cady, et al, 3 reported that differentiated types constitute 90% of thyroid carcinoma and, in the same report, he noted that through the four decades , undifferentiated forms became significantly less common, amounting to 9% over the period. Jacobs, et al, 11 in 1983, reported differentiated types constituted 81% of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the cases have a differentiated histology. 1,2,3 However, there has been no prior documented study on the incidence and geographical distribution of thyroid cancer in the Kingdom of Saudi Arabia. Accordingly, a retrospective study was conducted to assess the histological type, age and sex distribution of malignancy in all thyroid specimens resected at three major referral centers in Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…A striking female predominance is present in most series of differentiated thyroid carcinomas, especially below the age of 50 years (Cady et al, 1976;Akslen et al, 1990). Hormonal or other factors related to reproduction may, in part, explain this sex difference.…”
mentioning
confidence: 99%